Komunikasi antar Budaya dalam Masyarakat Multikultur (Studi Kasus pada Karyawan warga Negara Jepang dan Indonesia di PT. Tokyu Land Indonesia) - Anita Febiyana; Ade Tuti Turistiati (LUGAS Jurnal Komunikasi, 2019)
The purpose of this study was to analyze intercultural communication between Japanese and Indonesian employees at PT. Tokyu Land Indonesia. This research was also to analyze barriers which occurred in intercultural communication between them, and how to overcome these barriers. The method used in this study was a qualitative research method with a case study approach. Data collection was carried out by using an in-depth interview with 3 Japanese and 3 Indonesian employees, observation, and relevant previous research articles, and research-related documents. This research used the intercultural communication model of William B. Gudykunst and Young Yun Kim, intercultural communication concepts from Edward T. Hall, such as proxemics (the concept of distance), chronemics (the concept of time), high context and low context communication, individualism and collectivism, stereotypes. The results of the study showed that intercultural communication between Japanese and Indonesian employees at PT. Tokyu Land Indonesia is relatively good. Obstacles that occurred in intercultural communication are due to problems of differences and understanding of language, habits, respect for time (Japanese monochronic while Indonesia is polychronic), and the existence of stereotypes from each nation. To overcome these obstacles, they have to learn more about Japanese culture for Indonesian employees, and Indonesian culture for Japanese employees, openness to confirm understanding of the message delivered, mutual respect, and forgiveness each other if a misunderstanding occurs.